PSYCHOLOGICAL AND PHYSIOLOGICAL EFFECTS OF STRESS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Stress is a complex biopsychosocial phenomenon that significantly affects human health and well-being. This study aims to analyze the psychological and physiological impacts of stress, with a particular focus on its short-term adaptive functions and long-term pathological consequences. Acute stress can enhance cognitive performance and adaptive responses through activation of the sympathetic nervous system and the hypothalamic–pituitary–adrenal (HPA) axis. However, chronic stress leads to dysregulation of these systems, resulting in elevated cortisol levels, impaired immune function, and increased vulnerability to various diseases. From a psychological perspective, prolonged stress is strongly associated with emotional disturbances such as anxiety, depression, irritability, and cognitive impairments including reduced attention, memory deficits, and impaired decision-making. Physiologically, chronic stress contributes to the development of cardiovascular disorders, metabolic dysfunction, gastrointestinal disturbances, and weakened immune responses. The findings highlight the importance of early stress management interventions, including behavioral, cognitive, and lifestyle-based strategies such as physical activity, mindfulness practices, and social support. Understanding the multidimensional nature of stress is essential for developing effective prevention and treatment approaches aimed at improving overall health outcomes.